Clinical, epidemiological and molecular characteristics of Streptococcus uberis infections in dairy herds. - Zadoks, R. N. (Cambridge University Press, 2003)
A longitudinal observational study (18 months) was carried out in two Dutch dairy herds to explore clinical, epidemiological and molecular characteristics of Streptococcus uberis mastitis. Infections (n = 84) were detected in 70 quarters of 46 cows. Bacterial isolates were characterized at strain level by random amplified polymorphic DNA (RAPD) fingerprinting. Persistent infections were usually attributable to one strain, while recurrent infections could be caused by different strains. When multiple quarters of a cow were infected, infections were mostly caused by one strain. In each herd, multiple strains were identified yet one strain predominated. The majority of all infections were subclinical, and infections attributed to predominant strains were more chronic than infections attributed to other strains. Epidemiological and molecular data suggest infection from environmental sources with a variety of S. uberis strains as well as within-cow and between-cow transmission of a limited number of S. uberis strains, with possible transfer of bacteria via the milking machine.